2009
DOI: 10.1200/jco.2008.18.8938
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Selenium, Manganese Superoxide Dismutase, and Intermediate- or High-Risk Prostate Cancer

Abstract: A B S T R A C T PurposeIn vitro, in vivo, and epidemiologic studies support a role for selenium in reducing the risk of prostate cancer. Our group previously demonstrated a strong interaction between plasma selenium and the manganese superoxide dismutase (SOD2) gene and incident prostate cancer risk. We now hypothesized that SOD2 modifies the association between selenium level and risk of aggressive prostate cancer at diagnosis. Patients and MethodsWe assessed SOD2 variants and plasma selenium in 489 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
58
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 46 publications
7
58
1
Order By: Relevance
“…Additionally, several studies showed that Zn supplement may protect against free radical damage [16] or that Zn levels are decreased in patients with certain malignancies [17]. Se and Zn levels have been correlated to prostate cancer risk [18,19]; higher Se levels are related to a lower risk of many types of neoplasms, including lung, colorectal, prostate and possibly bladder [20,21]. Selenium is thought to inhibit carcinogenesis through many mechanisms including reduction of oxidative stress and inflammation, enhancement of the immune response, induction of apoptosis and cell cycle arrest as well as transactivation of DNA repairing genes [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several studies showed that Zn supplement may protect against free radical damage [16] or that Zn levels are decreased in patients with certain malignancies [17]. Se and Zn levels have been correlated to prostate cancer risk [18,19]; higher Se levels are related to a lower risk of many types of neoplasms, including lung, colorectal, prostate and possibly bladder [20,21]. Selenium is thought to inhibit carcinogenesis through many mechanisms including reduction of oxidative stress and inflammation, enhancement of the immune response, induction of apoptosis and cell cycle arrest as well as transactivation of DNA repairing genes [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…At the median overall follow-up of 5.46 years, hazard ratios (HRs) were higher, but not significantly so, for vitamin E (HR: 1.13; 99% CI: 0.95-1.35), selenium (HR: 1.04; 99% CI: 0.87-1.24) and vitamin E and selenium (HR: 1.05; 99% CI: 0.88-1.25) compared with placebo. Emerging data suggest that the chemopreventive effects of selenium may be dependent on the genetic variants of selenoproteins [18,19]. Archived tissue and blood from the SELECT trial are expected to help unravel these questions.…”
Section: Chemoprevention Trialsmentioning
confidence: 99%
“…There was evidence of an interaction between SOD2 and selenium levels such that among men with the AA genotype, higher selenium levels were associated with a reduced risk of presenting with aggressive disease (RR: 0.60; 95% CI: 0.32-1.12), whereas among men with a V allele, higher selenium levels were associated with an increased risk of aggressive disease (for VV or VA men, RR: 1.82; 95% CI: 1.27-2.61; P for interaction , 0.007). 12 Finally, it may be hypothesized that the positive effects of selenium in the NPC study and the positive effects of vitamin E on PCa incidence in the ATBC trial could have been due to chance in secondary analyses. In addition, recently published results from the Prostate Cancer Prevention Trial found no significant association between vitamin E and selenium and the incidence of PCa.…”
Section: Potential Prostate Cancer Preventive Agents Selenium and Vitmentioning
confidence: 99%